The Forgotten Era of "The Forgotten People": A Hidden History of Metis in Parkland, Saskatchewan, 1918-1965 ... - Andersen, Christian (University of Alberta Library, 2011)
SSHRC Awarded IG 2012: Few scholars would attempt to explain contemporary Canadian issues without reference to the massive changes of the twentieth century. Yet, Metis historiography has been dominated by 18th and 19th Century events (inside the discipline of history as well as out). This project seeks to demonstrate what more recent vernacular history may reveal about the simplistic correlations often drawn between historical events and contemporary Métis issues. In doing so, it seeks to disseminate this information not only among non-university educators (school teachers, etc.) but among the members of the Metis community as well. ...